21.2 mV/K High-Performance Ni(50 nm)-Au(100 nm)/Ga2O3/p-Si Vertical MOS Type Diode and the Temperature Sensing Characteristics With a Novel Drive Mode - Cicek, Osman; Arslan, Engin; Altindal, Semsettin; Badali, Yosef; Ozbay, Ekmel (Institute of Electrical and Electronics Engineers (IEEE), 2022)
IEEESensitivity (S) and drive mode are the crucial issues for the vertical metal-oxide-semiconductor (MOS) type diode applied in temperature sensing. In this study, experimentally, we indicated that the S values of the Ni(50nm)-Au(100nm)/Ga2O3/p-Si vertical MOS type diode, using the measured capacitance-voltage (Cm-V) outputs, are obtained with a novel drive mode. We applied the constant capacitance mode to drive the silicon thermo-diodes as well as constant current mode, and constant voltage mode, which are known as two different methods in the literature. Meanwhile, the S value is 21.2mV/K at 1nF. This value is the highest value proven in the literature excepting the cryogenic temperature region, and near the room temperature. This study provided an original structure for the silicon thermo-diodes and a novel way to drive them.
Keywords: Vertical metal-oxide-semiconductor (MOS) type diode; Sensitivity; Novel drive mode; Novel drive mode, sensitivity, temperature sensing, vertical metal-oxide-semiconductor (MOS) type diode.; Temperature sensing; 7. Clean energy